What is the average rate of change from x = −3 to x = −4?
Thank you for the opportunity to help you with your question!
post the graph
i will help you
where is the graph just put it here
i posted the graph
Sorry for late :
the average rate is :
a = (Y2 - Y1) / (X2 - X1) = ((-3) -(-1) ) / ((-3) - ( -4 ) ) = - 1
the average rate is : a = -1
Each time you have any other assignment please invite me i will give the best answer
-1 isnt an option.
Content will be erased after question is completed.
Enter the email address associated with your account, and we will email you a link to reset your password.
Forgot your password?